COLUMN STRUCTURAL WORK METHODS IN MULTI-STORY RESIDENTIAL BUILDING CONSTRUCTION - Reynold Andika Pratama; Adri Fato; Angga Jaya Dipringga; Agil Finalyanto (International Journal Multidisciplinary Science, 2025)
This study investigates the column structural work methods employed in the construction of a 4-story residential building in Pondok Indah, South Jakarta, focusing on preparation, execution, and quality control processes. Utilizing a qualitative observational approach during a professional internship, the research documents reinforcement fabrication, formwork installation, concrete placement, formwork removal, and curing practices. Key findings highlight the use of 16-25mm deformed bars for longitudinal reinforcement, plywood formwork with steel supports, and a 30 MPa concrete mix, with systematic procedures ensuring dimensional accuracy and structural integrity. Quality control measures, including plumbness checks, slump testing, and compressive strength verification, were critical to achieving compliance with project specifications. The study underscores the importance of precise reinforcement assembly, controlled concrete placement, and rigorous quality protocols in balancing theoretical design requirements with practical implementation. The methods demonstrated efficiency and quality, aligning with established standards while adapting to site-specific conditions. Recommendations for future projects include detailed planning for reinforcement, investment in quality formwork, comprehensive quality control, and worker training to enhance efficiency and durability. This research provides practical insights for civil engineers aiming to optimize column construction in multi-story residential buildings.